PUPPETRY : THE CARRIER OF TRADITIONAL FOLK MUSIC,CULTURE AND TRADITIONS - Tyagi, Namita; Poonam Kumari, (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian culture is reflected in various forms of art, in which folk art playing a significant role. Among the diverse forms of folk art, puppetry is also included. Puppetry is a multifaceted and dynamic art form that has been captivating audiences for centuries. In puppetry performances, music holds as much importance as emotional expression does in painting. From ancient traditions to contemporary theater, music serves as an essential element in puppetry, narrating the story, creating the appropriate atmosphere, and providing rhythm and form to the performance. In ancient civilizations such as India, China, and Indonesia, the art of puppetry was celebrated as a form of religious influence and cultural festivity. In its evolved form, puppetry has also contributed to education and psychology. In classrooms, it has served as an effective audio-visual aid for learning, leaving a positive impact on the audience. In public awareness campaigns, the plays and stories crafted through puppetry stimulate the human mind, with the sound of music playing a special role in enhancing the experience. This research paper explores the role of music in the traditional performance of puppetry, highlighting how music integrates with puppetry to create a positive impact. It presents the coordination of music in enhancing the overall effect of the puppetry performance.